2022
DOI: 10.1021/acsnano.2c07861
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Membrane-Coated Nano-Gemcitabine Promotes Lymphocyte Infiltration and Synergizes AntiPD-L1 to Restore the Tumoricidal Function

Abstract: The limited lymphocyte infiltration and exhaustion of tumoricidal functions in solid tumors remain a formidable obstacle to cancer immunotherapy. Herein, we designed a macrophage membrane-coated nano-gemcitabine system (MNGs) to promote lymphocyte infiltration and then synergized anti-programmed death ligand 1 (antiPD-L1) to reinvigorate the exhausted lymphocytes. MNGs exhibited effective intratumor-permeating and responsive drug-releasing capacity, produced notable elimination of versatile immunosuppressive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 50 publications
0
33
0
Order By: Relevance
“…Modifying immune cells through genetic engineering can further enhance the antitumor effect. Li et al designed a PD-L1 functionalized MMs-derived BNDS (MNGs) coating with gemcitabine to promote lymphocyte infiltration, and then cooperated with anti-PD-L1 to reactivate depleted lymphocytes. Based on this, MNGs can accumulate at the site of breast cancer and penetrate into the deep region of cancer, promoting the infiltration of lymphocytes to the intratumoral region by up-regulating the secretion of lymphocyte chemokines.…”
Section: Application Of Bnds In Tumor Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Modifying immune cells through genetic engineering can further enhance the antitumor effect. Li et al designed a PD-L1 functionalized MMs-derived BNDS (MNGs) coating with gemcitabine to promote lymphocyte infiltration, and then cooperated with anti-PD-L1 to reactivate depleted lymphocytes. Based on this, MNGs can accumulate at the site of breast cancer and penetrate into the deep region of cancer, promoting the infiltration of lymphocytes to the intratumoral region by up-regulating the secretion of lymphocyte chemokines.…”
Section: Application Of Bnds In Tumor Immunotherapymentioning
confidence: 99%
“…Modifying immune cells through genetic engineering can further enhance the antitumor effect. Li et al 81 It is generally believed that NK cells play a vital role in the fight against cancer and infection due to their ability to release cytotoxic factors and mediate apoptosis through receptor activation. With the help of membrane proteins, such as RANKL and DNAM-1, activated NK cells can synthesize and secrete various cytokines to regulate immunity and hematopoiesis and directly kill target cells.…”
Section: Macrophages and Macrophage Membranes (Mms)mentioning
confidence: 99%
“…Recently, increasing attention has been paid to biomimetic drug delivery systems, especially cell membrane-coated nanoparticles (NPs) . Nanoparticles camouflaged by biological cell membranes have recently been the focus of attention for their prolonged circulation in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, increasing attention has been paid to biomimetic drug delivery systems, especially cell membrane-coated nanoparticles (NPs). 13 Nanoparticles camouflaged by biological cell membranes have recently been the focus of attention for their prolonged circulation in vivo. 14 Its intrinsic self-recognition properties optimize its dynamic properties by masking its contents to avoid clearance by the mononuclear phagocyte system (MPS) and immune surveillance.…”
Section: Introductionmentioning
confidence: 99%
“…Immunotherapy with immune checkpoint inhibitors (ICBs) has exhibited prominent clinical effects in the treatment of various tumors. However, several challenges such as low response rates and therapeutic resistance still hinder the clinical application. It has been demonstrated that the immunosuppressive tumor microenvironment (TME) including acidic, hypoxic conditions and immunosuppressive immune cells, causes the relatively poor clinical efficacy of ICBs . Growing evidence has indicated that aerobic glycolysis, characteristic of tumor metabolism, is the leading cause of an immunosuppressive TME .…”
mentioning
confidence: 99%